(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Financial inclusion, which aims to provide access to affordable and reliable financial services to underserved populations, is crucial for promoting economic growth and reducing poverty. In recent years, the emergence of financial technology (Fintech) has shown great potential in advancing financial inclusion by offering innovative solutions and leveraging technology to overcome traditional barriers. This research paper examines the role of Fintech in enhancing financial inclusion, focusing on the challenges and opportunities it presents. The paper begins with an overview of financial inclusion and its significance in addressing socio-economic disparities. It explores the concept of Fintech and its various forms, including mobile banking, digital wallets, peer-to-peer lending, and crowd funding. A comprehensive literature review is conducted to understand the challenges faced by underserved populations in accessing financial services, and the potential of Fintech in addressing these challenges is explored. Methodologically, a mixed methods approach is adopted, combining qualitative and quantitative research methods. Primary data is collected through surveys and interviews, targeting both Fintech users and non-users from diverse socio-economic backgrounds. Secondary data sources are also utilized to support the analysis. The findings of the study reveal the positive impact of Fintech in enhancing financial inclusion. Fintech solutions have significantly improved access to financial services, reduced costs, and increased financial literacy among underserved populations. However, several challenges hinder the full potential of Fintech. These challenges include regulatory and legal constraints, technological barriers, and socio-economic and cultural factors. This research paper contributes to the existing literature by providing insights into the role of Fintech in enhancing financial inclusion. It identifies challenges and opportunities associated with fintech adoption and offers recommendations for policymakers, financial institutions, and fintech companies to create an enabling environment for inclusive financial services. The findings underscore the importance of leveraging fintech’s potential to achieve sustainable financial inclusion and foster economic development.